2007
DOI: 10.1073/pnas.0701179104
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Par-1b/MARK2 polarity kinase leads to increased metabolic rate, decreased adiposity, and insulin hypersensitivity in vivo

Abstract: Obesity is a major factor central to the development of insulin resistance and type 2 diabetes. The identification and characterization of genes involved in regulation of adiposity, insulin sensitivity, and glucose uptake are key to the design and development of new drug therapies for this disease. In this study, we show that the polarity kinase Par-1b/MARK2 is required for regulating glucose metabolism in vivo. Mice null for Par-1b were lean, insulin hypersensitive, resistant to high-fat diet-induced weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 58 publications
5
67
0
Order By: Relevance
“…Recent studies have demonstrated that AMPK regulates tight junction assembly and cell polarity in mammalian cells and in Drosophila in a manner linked to the response to energy stress (28,51,52). Mouse knockouts of MARK2 show metabolic defects (19). Collectively, these data support the view that energy sensing and cell polarity may be broadly integrated under the control of LKB1-AMPK signaling.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Recent studies have demonstrated that AMPK regulates tight junction assembly and cell polarity in mammalian cells and in Drosophila in a manner linked to the response to energy stress (28,51,52). Mouse knockouts of MARK2 show metabolic defects (19). Collectively, these data support the view that energy sensing and cell polarity may be broadly integrated under the control of LKB1-AMPK signaling.…”
supporting
confidence: 71%
“…The AMPK/MARK/SAD subfamily kinases can be activated by the Lkb1-mediated phosphorylation of a threonine residue in their activation loops (30). AMPKs, MARKs, and SADs are potential mediators of the Lkb1-dependent regulation of epithelial polarity, through their roles in the establishment of tight junctions and the regulation of tubulin dynamics (14,15,19,28,51,52). Western blotting analyses of PD1 pancreatic lysates demonstrated greatly reduced phosphorylation of AMPK, MARK2 and MARK3, and SAD-B in the p-Lkb1 pancreas.…”
Section: Resultsmentioning
confidence: 99%
“…If a kinase directly phosphorylated their putative substrate, the kinase would never choose a cell type, hepatocytes, or model cells (HEK293), and regulate the cellular downstream cascades of the substrate in the same manner, which may deny that AMPK is the CRTC2 kinase in hepatocytes. However, it does not deny the contribution of AMPK to gluconeogenesis in hepatocytes (36), although we have to mention here that other AMPK family kinases, MARKs (37,38), may be capable of phosphorylating CRTC in cells (32,39).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of the MARK2 and MARK3 kinases have recently been studied using targeted gene knockout approaches in mice (5,6). Two independently derived mouse lines null for MARK2 have implicated this protein kinase in diverse physiological processes, including fertility (7), immune system homeostasis (8), learning and memory (9), and glucose homeostasis and energy metabolism (6).…”
mentioning
confidence: 99%